Attosecond pump–attosecond probe spectroscopy of Auger decay. Issue 21 (24th May 2021) - Kissin, Yoel; Ruberti, Marco; Kolorenč, Přemysl; Averbukh, Vitali
Abstract : Attosecond pump–attosecond probe spectroscopy maps Auger decay dynamics on the ionic charge state populations, in analogy to time resolving photodissociation in femtochemistry. Abstract : Attosecond pump–attosecond probe spectroscopy is becoming possible due the development of sub-femtosecond free electron laser (FEL) pulses as well as intense high-order harmonic generation-based attosecond sources. Here we investigate theoretically whether these developments can provide access to direct time-resolved measurement of Auger decay through detection of the total yield of an ionic decay product, in analogy to the photodissociation product detection in femtochemistry. We show that the ion yield based measurement is generally possible and in the case of the inner-valence hole decay can be background-free. Extensive first principles calculations are used to optimise the probe photon energies for a variety of prototypical systems.